E-commerce challenge within B2C transactions inside EU countries - Martynkiewicz-Frank, Monika (Research Papers of Wrocław University of Economics, 2018)
Following the technology development, consumer habits change. Traders of goods seek new channels to reach the end customer, and online trading becomes more and more attractive. The European Union has already realised that harmonisation of VAT tax law is the key issue to reduce fraud on intra-community transactions, and simplifying the regulations for traders dealing on the internal market, would bring positive impact for the whole economy. Nevertheless, existing regulations, based on traditional commercial transaction models, make administrative taxation related to them very expensive and may provide the traders with a large tax risk in every country in which the trader handles the transaction. In the paper the authoress describes the common problems with covering sales margin due to changes in the reported revenue due to VAT regulations, as well as the obligation to provide to the end customer the gross price including VAT
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 515; s. 157-165
Keywords: VAT; VAT compliance; online trading; e-commerce; B2C; rozliczenia VAT; handel online